Destruction of endocrine disruptor compounds (EDCs) with combined OzoneUVH2O2 process - Muhammad Firdaus Kamsani (Nanyang Technological University, 2020)
Bisphenol A (BPA) is an organic synthetic compound with a chemical formula of (CH₃)₂C(C₆H₄OH)₂ . It is one of the highest volume chemicals used in making plastic worldwide, with over 6 million pounds produced each year. BPA is one of the main components in the production of various plastic products. BPA is a well-known endocrine disrupting compound (EDC) as it can inhibit the hormonal system of the organism (Julia C.A., Bradley J.P., 2016). Furthermore, being a non-biodegradable, it can harm the food chain through bioaccumulation and biomagnification (Shiye Zhao et al., 2014). Several methods have been explored to remove bisphenol A. including advanced oxidation processes which are the most effective methods. In this study, the degradation of BPA was investigated by a combined UV/Ozone and hydrogen peroxide (H2O2) advanced oxidation process. High Performance Liquid Chromatography (HPLC) and Total Organic Carbon (TOC) Analyzer were used to evaluate the degradation rate and the mineralization kinetics of BPA, respectively. The degree of degradation and mineralization of BPA was carried out by investigating the effect of BPA concentration, ozone concentration, H2O2 concentration, UV intensity and pH. The experiments were carried out by changing the concentration of one of these parameters while keeping the rest of parameters constants to investigate the impact of each of these parameters on BPA degradation and mineralization. Increasing BPA concentration will only slow down the degradation rate as there will be more BPA compounds in the water to be treated. Increasing ozone feed rate will help to speed up the rate of degradation rate as there will be more ozone in the water to photolyzed to form more hydroxyl radicals. With increase in concentration of hydroxyl radicals, this will lead to a faster rate of reaction with BPA molecules and thus increasing the rate of degradation. Increasing the pH level of the solution have shown to hasten the kinetic reaction of the BPA removal. This is due to formation of hydroxyl radical is ore favoured when pH level is higher. Thus, more hydroxyl radicals form, which result in the increase in BPA removal rate. Increasing the Lamp intensity also have shown an increase in BPA removal rate. This is due to its ability to split the hydrogen peroxide and ozone molecules to form hydroxyl molecules which will help to degrade the BPA. However, with said, UV lamp intensity will reach its optimum once hydrogen peroxide and ozone concentration become a limiting reactant. Increasing concentration of hydrogen peroxide have shown the most effect in the rate of BPA removal. This is due to each hydrogen peroxide molecule ability to split into 2 hydroxyl molecules under the influence of UV light. This is more compared to increasing ozone feed rate.